Imaging and admission practices in paediatric head injury across emergency departments in Australia and New Zealand: A PREDICT study. (26th November 2019) - Phillips, Natalie; Dalziel, Stuart R; Borland, Meredith L; Dalton, Sarah; Lyttle, Mark D; Bressan, Silvia; Oakley, Ed; Hearps, Stephen JC; Kochar, Amit; Furyk, Jeremy; Cheek, John A; Gilhotra, Yuri; et al.
Abstract: Objectives: Variation in the management of paediatric head injury has been identified worldwide. This prospective study describes imaging and admission practices of children presenting with head injury across 10 hospital EDs in Australia and New Zealand. Methods: Prospective observational multicentre study of 20 137 children (under 18 years) as a planned secondary analysis of the Australasian Paediatric Head Injury Rules Study. All presentations with head injury without prior imaging were eligible for inclusion. Variations in rates of computed tomography of the brain (CTB) and admission practices between sites, ED type and country were investigated, as were clinically important traumatic brain injuries (ciTBIs) and abnormal CTBs within CTBs. Results: Among the 20 137 enrolled patients, the site adjusted CTB rate was 11.2% (95% confidence interval [CI] 7.8–14.6); individual sites ranged from 2.6 to 18.6%. ciTBI was found in 0.4–2.2%, with abnormal scans documented in 0.7–6.5%. As a percentage of CTBs undertaken, ciTBIs were found in 12.8% (95% CI 10.8–14.7) with individual site variation of 8.8–16.9%, and no statistically significant difference noted, and traumatic abnormalities in 29.3% (95% CI 26.2–32.3) with individual site variation between 19.4 and 35.6%. Among those under 2 years, traumatic abnormalities were found in greater than 50% of CTBs at 90% of sites. Admission rate overall was 24.0% (site adjusted) with wide variation between sites (5.0–48.9%). Conclusion: Across the 10 largely tertiary EDs included in this study, the overall CTB rate was low with no significant variation between sites when adjusted for ciTBIs.